2022
DOI: 10.1002/advs.202104823
|View full text |Cite
|
Sign up to set email alerts
|

A Temporal PROTAC Cocktail‐Mediated Sequential Degradation of AURKA Abrogates Acute Myeloid Leukemia Stem Cells

Abstract: AURKA is a potential kinase target in various malignancies. The kinase‐independent oncogenic functions partially disclose the inadequate efficacy of the kinase inhibitor in a Phase III clinical trial. Simultaneously targeting the catalytic and noncatalytic functions of AURKA may be a feasible approach. Here, a set of AURKA proteolysis targeting chimeras (PROTACs) are developed. The CRBN‐based dAurA383 preferentially degrades the highly abundant mitotic AURKA, while cIAP‐based dAurA450 degrades the lowly abunda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…However, only CRBN and VHL are the two most commonly employed ligases. Notably, several orally bioavailable CRBN-recruited bifunctional degraders have entered clinical trials. Therefore, several CRBN- and VHL-recruited degraders were first synthesized by converting the pyrrolidine group of PXA13 to piperazine to attach the linker and E3 ligase ligand (Figure ). In the first round of design, it was found that CRBN-recruited degraders showed stronger antiproliferative activities against FLT3-ITD-positive AML cells MV4-11 and MOLM-13 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…However, only CRBN and VHL are the two most commonly employed ligases. Notably, several orally bioavailable CRBN-recruited bifunctional degraders have entered clinical trials. Therefore, several CRBN- and VHL-recruited degraders were first synthesized by converting the pyrrolidine group of PXA13 to piperazine to attach the linker and E3 ligase ligand (Figure ). In the first round of design, it was found that CRBN-recruited degraders showed stronger antiproliferative activities against FLT3-ITD-positive AML cells MV4-11 and MOLM-13 (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is of great significance to develop more E3 ligands and explore the possibility of PROTAC‐induced POI degradation by other E3 ligases in the future. At the same time, it is also beneficial to develop tissue‐specific PROTACs according to the different tissue expression of E3 ligases and to develop cell cycle‐specific PROTACs or concomitant drugs according to the dynamic expression process of E3 ligases in the cell cycle 162 . In addition, in order to better deal with the drug resistance caused by the bypass signal pathway mechanism, it is also worth exploring suitable bypass targets, designing a reasonable combination strategy, or developing dual‐target PROTAC degradants.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…This is relevant because several studies with PROTACs indicate efficient degradation of WDR5 by VHL but not by CRBN 29,31 . In contrast, CRBN-based PROTACs have been shown to efficiently degrade the mitotic kinase Aurora A 10,11,[33][34][35] . We therefore tested whether VHL and CRBN are able to degrade Aurora A in the RiPA system.…”
Section: Ripa Correctly Predicts Suitability Of E3 Ligases For Wdr5 P...mentioning
confidence: 98%